Antimicrobial activity of the heliangolide chromolaenide and related sesquiterpene lactones - Ciccio, José (1980)
Some sesquiterpene lactones are known to exhibit antimicrobial activity [1, 2]. More recently, it has been noted that the pseudoguainolide carpesiolin inhibits the growth of Xanthomonas oryzae [3]. Here, we report on the antimicrobial activity of the heliangolide chromolaenide 1, isolated from Chromolaena glaberrima (DC.) King et Robinson [4] and its derivatives, against Staphylococcus aureus. The results are summarized in Table 1. It is apparent that there is a clear dependence between antimicrobial activity and the presence of the t~-methylene-3,- iactone group. As already established [5-8], the growth inhibition of microorganisms is caused by the alkylation of their nucleophilic centers (R-SH) with the unsaturated lactone moiety. This observation is congruent with our results, because the only inactive compound was 3, which is the one with no unsaturated lactone.